Process and energy analysis of pelleting agricultural and woody biomass blends - Harun, N.Y. (MDPI AG, 2018)
Unprocessed biomass has low energy density and high transportation cost. The energy generated through biomass can be enhanced by the pelletizing technique. In order to evaluate the energy requirement for the pelletizing of agricultural biomass, three different particle sizes (150-300, 300-425, and 425-600 Î¼m) of reed canary grass (RCG), timothy hay (TH), and switchgrass (SW) were selected in the present work. Furthermore, two woody biomasses (spruce and pine) were also considered under similar experimental conditions for comparison purposes. An Instron machine attached to an in-house built pelletizer unit was employed to produce a single pellet. The energy demand for compacting ground biomass (spruce) with a particle size of 150 Î¼m was lower (2.07 kJ) than those required for particle sizes of 300 Î¼m (2.24 kJ) and 425 Î¼m (2.43 kJ). The energy required for compacting ground reed canary grass, timothy hay, and switchgrass was lower (1.61, 1.97, and 1.68 kJ, respectively) than that required for spruce (2.36 kJ) and pine (2.35 kJ), evaluated at a 159-MPa load and at temperature of about 80 Â°C. The energy demand for blended biomass was around 2 kJ with the pellet quality approaching that of the pellets made from woody biomass. Overall, blending helped to improve the quality of pellets and lower the compaction energy requirements. Â© 2018 by the authors.